Transcatheter aortic valve implantation versus surgical aortic valve replacement for severe aortic stenosis in people with low surgical risk - Kolkailah, Ahmed A (Cochrane Database Syst Rev, 2019)
BACKGROUND: Severe aortic valve stenosis (AS) is a major cause of morbidity and mortality worldwide. The definitive management for severe AS is aortic valve replacement (AVR). The choice of transcatheter approach versus open‐heart surgery for AVR in people with severe AS and low surgical risk remains a matter of debate. OBJECTIVES: To assess the benefits and harms of transcatheter aortic valve implantation (TAVI) compared to surgical aortic valve replacement (SAVR) in people with severe AS and low surgical risk. SEARCH METHODS: We searched the following databases for randomised controlled trials (RCTs) on 29 April 2019: Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, and Web of Science Core Collection. We also searched ClinicalTrials.gov and the World Health Organization International Clinical Trials Registry Platform. We searched all databases from inception to present and imposed no restriction on language or date of publication. SELECTION CRITERIA: We included RCTs that compared TAVI and SAVR in adults (18 years of age or older) with severe AS and low surgical risk. DATA COLLECTION AND ANALYSIS: We used the standard methodological procedures expected by Cochrane. Two authors independently screened titles and abstracts for inclusion, performed data extraction, and assessed risk of bias in the studies included. We analysed dichotomous data using the risk ratio (RR) and continuous data using the mean difference (MD), with respective 95% confidence intervals (CI). We assessed the certainty of evidence for each outcome using the GRADE approach. Our outcomes of interest were assessed in the short term (i.e. during hospitalisation and up to 30 days of follow‐up). Primary outcomes were all‐cause mortality, stroke, and rehospitalisation. Secondary outcomes were myocardial infarction (MI), cardiac death, length of hospital stay (LOS), permanent pacemaker (PPM) implantation, new‐onset atrial fibrillation, acute kidney injury (AKI), and any bleeding. MAIN RESULTS: We identified four studies (13 reports), with 2818 participants, and one ongoing study. Overall certainty of evidence ranged from high to very low. There is probably little or no difference between TAVI and SAVR for the following short‐term outcomes: all‐cause mortality (RR 0.69, 95% CI 0.33 to 1.44; SAVR 11 deaths per 1000, TAVI 8 deaths per 1000 (95% CI 4 to 16); 2818 participants; 4 studies; moderate‐certainty evidence); stroke (RR 0.73, 95% CI 0.42 to 1.25; SAVR 21 strokes per 1000, TAVI 16 strokes per 1000 (95% CI 9 to 27); 2818 participants; 4 studies; moderate‐certainty evidence); MI (RR 0.82, 95% CI 0.42 to 1.58; SAVR 14 MI per 1000, TAVI 11 MI per 1000 (95% CI 6 to 21); 2748 participants; 3 studies; moderate‐certainty evidence); and cardiac death (RR 0.71, 95% CI 0.32 to 1.56; SAVR 10 cardiac deaths per 1000, TAVI 7 cardiac deaths per 1000 (95% CI 3 to 16); 2818 participants; 4 studies; moderate‐certainty evidence). TAVI may reduce the risk of short‐term rehospitalisation, although the confidence interval also includes the possibility of no difference in risk between groups (RR 0.64, 95% CI 0.39 to 1.06; SAVR 30 cases per 1000, TAVI 19 cases per 1000 (95% CI 12 to 32); 2468 participants; 2 studies; low‐certainty evidence). TAVI, compared with SAVR, probably increases the risk of PPM implantation (RR 3.65, 95% CI 1.50 to 8.87; SAVR 47 per 1000, TAVI 170 cases per 1000 (95% CI 70 to 413); number needed to treat for an additional harmful outcome (NNTH) = 7; 2683 participants; 3 studies; moderate‐certainty evidence). We are uncertain whether TAVI, compared with SAVR, affects the LOS in days, although it appears to be associated with shorter LOS. TAVI, compared with SAVR, reduces the risk of atrial fibrillation (RR 0.21, 95% CI 0.15 to 0.30; 2683 participants; 3 studies), AKI (RR 0.30, 95% CI 0.16 to 0.58; 2753 participants; 4 studies), and bleeding (RR 0.31, 95% CI 0.16 to 0.62; 2753 participants; 4 studies) (all high‐certainty evidence). AUTHORS' CONCLUSIONS: Our meta‐analysis indicates that, in the short term, TAVI probably has little or no mortality difference compared to SAVR for severe AS in individuals with low surgical risk. Similarly, there is probably little or no difference in risk of stroke, MI, and cardiac death between the two approaches. TAVI may reduce the risk of rehospitalisation, but we are uncertain about the effects on LOS. TAVI reduces the risk of atrial fibrillation, AKI, and bleeding. However, this benefit is offset by the increased risk of PPM implantation. Long‐term follow‐up data are needed to further assess and validate these outcomes, especially durability, in the low surgical risk population.